2021
DOI: 10.1038/s41467-021-27107-9
|View full text |Cite
|
Sign up to set email alerts
|

Acyl carrier protein promotes MukBEF action in Escherichia coli chromosome organization-segregation

Abstract: Structural Maintenance of Chromosomes (SMC) complexes act ubiquitously to compact DNA linearly, thereby facilitating chromosome organization-segregation. SMC proteins have a conserved architecture, with a dimerization hinge and an ATPase head domain separated by a long antiparallel intramolecular coiled-coil. Dimeric SMC proteins interact with essential accessory proteins, kleisins that bridge the two subunits of an SMC dimer, and HAWK/KITE proteins that interact with kleisins. The ATPase activity of the Esche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
1
10
2
Order By: Relevance
“…It has been reported that the MukB ATPase activity is DNA-independent and is, in fact, inhibited somewhat by double-stranded DNA (31), whereas Zawadzka et al (41) showed that DNA neutralized to some extent the effect of MukE-mediated inhibition of the MukBF ATPase activity. However, in our current study, using saturating concentrations of AcpP, which is required for the MukBF ATPase activity (25), we find no effect of DNA on the ATPase activity of either the MukBF or MukBEF complexes.…”
Section: Structural Bases For the Effects Of Mutagenesis On The Mukbe...contrasting
confidence: 81%
See 2 more Smart Citations
“…It has been reported that the MukB ATPase activity is DNA-independent and is, in fact, inhibited somewhat by double-stranded DNA (31), whereas Zawadzka et al (41) showed that DNA neutralized to some extent the effect of MukE-mediated inhibition of the MukBF ATPase activity. However, in our current study, using saturating concentrations of AcpP, which is required for the MukBF ATPase activity (25), we find no effect of DNA on the ATPase activity of either the MukBF or MukBEF complexes.…”
Section: Structural Bases For the Effects Of Mutagenesis On The Mukbe...contrasting
confidence: 81%
“…Optimal Conditions for the MukB ATPase Activity-MukB alone hydrolyzes ATP (26), and this activity is stimulated by MukF (27,28), whereas the MukBF ATPase is inhibited by MukE (27,28). AcpP was known to interact with MukB (26,29,30), but the significance of this interaction remained obscure until Prince et al (25) demonstrated that AcpP was required for maximal MukBF ATPase activity. This observation indicated that some previous observations of the MukB ATPase activity might have been affected by the extent to which the MukB preparation was saturated with AcpP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AcpP was known to interact with MukB ( 27 , 30 , 31 ), but the significance of this interaction remained obscure until Prince et al. ( 26 ) demonstrated that AcpP was required for maximal MukBF ATPase activity. This observation indicated that some previous observations of the MukB ATPase activity might have been affected by the extent to which the MukB preparation was saturated with AcpP.…”
Section: Resultsmentioning
confidence: 99%
“…This bent conformation of MukB had been reported previously ( 13 ). AcpP has also very recently been shown to be required for the MukB ATPase ( 26 ).…”
mentioning
confidence: 99%